2015
DOI: 10.7554/elife.10518
|View full text |Cite
|
Sign up to set email alerts
|

Temporal transcriptomics suggest that twin-peaking genes reset the clock

Abstract: The mammalian suprachiasmatic nucleus (SCN) drives daily rhythmic behavior and physiology, yet a detailed understanding of its coordinated transcriptional programmes is lacking. To reveal the finer details of circadian variation in the mammalian SCN transcriptome we combined laser-capture microdissection (LCM) and RNA-seq over a 24 hr light / dark cycle. We show that 7-times more genes exhibited a classic sinusoidal expression signature than previously observed in the SCN. Another group of 766 genes unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 54 publications
3
80
0
1
Order By: Relevance
“…Circadian clocks can generate rhythms with periods other than 24 h. Recent work has revealed two peaks of activation per circadian cycle in a subset of genes in the mammalian suprachiasmatic nucleus (Pembroke et al, 2015). 12-h oscillations have also been observed in peripheral mammalian tissues, including the liver (Hughes et al, 2009;Cretenet et al, 2010), bone marrow (Chen et al, 2000) and testis (Liu et al, 2007) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian clocks can generate rhythms with periods other than 24 h. Recent work has revealed two peaks of activation per circadian cycle in a subset of genes in the mammalian suprachiasmatic nucleus (Pembroke et al, 2015). 12-h oscillations have also been observed in peripheral mammalian tissues, including the liver (Hughes et al, 2009;Cretenet et al, 2010), bone marrow (Chen et al, 2000) and testis (Liu et al, 2007) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Because more and more cycling genes have been identified, the collection and integration of the data is helpful for further experimental consideration. Previously, four major databases were developed for circadian genes, including DIURNAL (23), CircaDB (29), SCNseq (30) and Bioclock (3133). The DIURNAL database maintains circadian microarray data for three plants, including Arabidopsis thaliana , poplar and rice (23).…”
Section: Introductionmentioning
confidence: 99%
“…73636034, probe RP_050825_02_B04coronal). A recent study also found that Hrh3 expression varies rhythmically in the SCN with peak levels found in the late day (Pembroke et al 2015). There is strong evidence that HA can phase-shift the circadian neural activity rhythms in rodent SCN slices (Cote and Harrington 1993;Meyer et al 1998;Biello 2009;Kim et al 2015).…”
Section: Discussionmentioning
confidence: 89%